2019
DOI: 10.1111/jth.14450
|View full text |Cite
|
Sign up to set email alerts
|

Trauma‐induced coagulopathy: The past, present, and future

Abstract: Trauma remains a leading cause of death worldwide, and most early preventable deaths in both the civilian and military settings are due to uncontrolled hemorrhage, despite paradigm advances in modern trauma care. Combined tissue injury and shock result in hemostatic failure, which has been identified as a multidimensional molecular, physiologic and clinical disorder termed trauma-induced coagulopathy (TIC).Understanding the biology of TIC is of utmost importance, as it is often responsible for uncontrolled ble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
189
0
24

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 206 publications
(216 citation statements)
references
References 99 publications
3
189
0
24
Order By: Relevance
“…Trauma‐induced coagulopathy is driven by two distinct and synergistic insults: hypovolemic shock due to blood loss and extensive tissue disruption (Figure ) . The variables that modify the TIC phenotype and course include (a) trauma: injury extent and severity, tissue type injured (head, orthopaedic), degree of hemorrhagic shock, mechanism of injury (blunt, penetrating/hemorrhagic), and time from injury; (b) patient factors: age, sex, medical comorbidities (cardiovascular disease), concomitant anticoagulant use, presence of other toxins including alcohol, heritable differences in baseline coagulation; and (c) resuscitation strategies: types of fluids used, the impact of blood components, adjuncts such as TXA, and timing of surgical intervention . The combination of these three variables distinguishes TIC from the other acute coagulopathies (ie, open cardiovascular surgery, liver transplantation, postpartum hemorrhage, sepsis, malignancy, and autoimmune‐ and toxin‐mediated coagulopathy) .…”
Section: Current Understanding Of the Mechanisms Of Trauma‐induced Comentioning
confidence: 99%
See 2 more Smart Citations
“…Trauma‐induced coagulopathy is driven by two distinct and synergistic insults: hypovolemic shock due to blood loss and extensive tissue disruption (Figure ) . The variables that modify the TIC phenotype and course include (a) trauma: injury extent and severity, tissue type injured (head, orthopaedic), degree of hemorrhagic shock, mechanism of injury (blunt, penetrating/hemorrhagic), and time from injury; (b) patient factors: age, sex, medical comorbidities (cardiovascular disease), concomitant anticoagulant use, presence of other toxins including alcohol, heritable differences in baseline coagulation; and (c) resuscitation strategies: types of fluids used, the impact of blood components, adjuncts such as TXA, and timing of surgical intervention . The combination of these three variables distinguishes TIC from the other acute coagulopathies (ie, open cardiovascular surgery, liver transplantation, postpartum hemorrhage, sepsis, malignancy, and autoimmune‐ and toxin‐mediated coagulopathy) .…”
Section: Current Understanding Of the Mechanisms Of Trauma‐induced Comentioning
confidence: 99%
“…The presentation is chiefly thought to be a result of the variability of the magnitude and timing of the interaction between tissue injury and shock as well as resuscitation practices. Variations in experimental measurements such as timing of patient presentation, prior therapy, and timing to blood sampling complicate the definition of TIC …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that the main causes of coagulation factor depletion in trauma patients are consumption and capillary leak syndrome due to disseminated intravascular coagulation (DIC), and consumptive thrombohemorrhagic disorder is the main pathophysiology of DIC. 2,3 Table 2 in the original review 1 shows high levels of thrombin-antithrombin III complex (TAT) and prothrombin fragment 1 + 2 (PF1 + 2). These changes reflect the increased thrombin generation, while table 2 shows decreased levels of thrombin.…”
Section: The Mechanis Ms Underlying Coag Ul Ation Fac Tor Deple Tionmentioning
confidence: 99%
“…Hemorrhage represents the most common cause of preventable death following severe injury, and a rapid response to stop bleeding is essential as exsanguination drives early mortality . Bleeding from injuries can be exacerbated by trauma‐induced coagulopathy, which involves impaired thrombin generation, platelet dysfunction, and altered fibrinolysis . Inhibition of fibrinolysis with tranexamic acid (TXA) in trauma patients at risk of bleeding demonstrates a reduction in mortality when treated within 3 h of injury, while treatment after 3 h increases bleeding risk .…”
mentioning
confidence: 99%